Integrating cultural heritage with the development of blue economy in Kenya: a framework for holding the state accountable - Ngulu, Joshua Mbinda (2024)
The Government of Kenya (GoK) has conceptualized the Vision-2030 blueprint to create ‘a globally competitive and prosperous middle-income country by 2030’. To attain this vision, Kenya has prioritized on investing in Blue Economy (BE). One of the main BE and 2030 flagship projects is the USD$5 Billion Lamu Port which is part of the multi-billion (USD$24-30 Billion) Lamu-Port-South-Sudan-Ethiopia-Transport (LAPSSET) Corridor project which traverses a vast region of great physical, socio-cultural, and economic diversity, and runs through or near sites renowned for their cultural and/or natural heritage, such as the Lamu Archipelago-a gazetted UNESCO World Heritage Site since 2002. The project is located in an indigenous peoples’ (IPs) territory who are poorer, marginalized, and more disadvantaged than other communities, their rights are not respected and not included in the BE development agenda or other participatory planning processes. Although the economic value generated from the BE makes one of the world’s largest economies, this thesis underscores the view that its skewed development, characterized by the marginalization of women, youth and IPs is a major challenge that must be overcome for the positive effect of the BE to be realized nationally and globally. The GoK has denied the IPs the right to participate in the conceptualization of the project so as to have their critical issues addressed and/or mitigated. This thesis addresses the overarching question, ‘How can the adverse effects emanating from the development of BE in Kenya be addressed to make the process participatory, accountable, transparent, equitable and inclusive, in order to be responsive to the present and future human uses and needs, including the needs of minorities, IPs and the most vulnerable groups in the society?’ Through the principle of Free, Prior and Informed Consent, this thesis makes a case for a framework for holding the state accountable when participating in BE development in IPs’ territories.